Interreligious Dialogue Includes Listening to Secular Voices - Baum, Gregory (Toronto journal of theology, 2016)
In this article I present several reasons why interreligious dialogue should include secular thinkers concerned with religion. Pope Benedict xvi appears to agree. In 2004, he engaged in a public dialogue with Habermas, in 2007 he quoted Adorno and Habermas in his encyclical Spes salvi, and in 2008 he fostered dialogue with secular thinkers by founding the Courtyard of the Gentiles in Rome, a reference to a courtyard in the Jerusalem Temple open to non-Jewish visitors.